Move : how decisive leaders execute strategy despite obstacles, setbacks, and stalls - Azzarello, Patty (Gildan Audio, 2020)
Move past the obstacles and implement your new strategyMove is your guide to mobilizing your whole organization to take your business forward. Whatever your needed transformation may be: a new initiative, a new market, a new product, your fresh strategy is up against a powerful foe: an organization's tendency to stay very busy and completely engaged what it's already doing. This book shows you how to cut through resistance and get your team engaged and proactively doing the new thing! Author Patty Azzarello draws on over twenty-five years of international business management experience to identify the chronic challenges that keep organizations from decisively executing strategy, and to give you a practical game plan for breaking through. Leaders tend to assume that stalls in execution are inevitable, unchanging parts of the workplace-but things can change. At the heart of every execution problem is the fact that there simply are not enough people doing what the business needs. This guide shows you how to get your entire organization on board-remove the fear, excuses, and hurdles-and uphold the new pursuit against distractions and dissent.No transformation can succeed without suitable engagement from the whole organization, but building engagement can be difficult, uncomfortable, and tentative. This book shows you how to get it done.